The assessment and pharmacological management of osteoporosis after admission for minimal‐trauma fracture at a major metropolitan centre. (28th November 2020) - Hopkins, Ria E.; Warner, Victoria; Sztal‐Mazer, Shoshana; Poole, Susan; Page, Amy
Abstract: Introduction: Significant evidence‐to‐practice gaps in osteoporosis management have led to national guidelines, the impact of which is unknown. We evaluated osteoporosis assessment and management after hospital admission to a major metropolitan centre with minimal trauma fracture (MTF) in the context of Australian osteoporosis guidelines. Method: This retrospective analysis included patients over 50 years of age who were admitted to hospital for over 48 h with MTF from 1st January to 31st December 2015. All emergency department (ED) presentations for fracture were identified by diagnosis coding, and 60% were randomly selected for hand‐screening to exclude traumatic, pathological, facial and digit fractures. Data were collected from medical records, and inpatient and discharge osteoporosis management was compared to Australian guideline recommendations. Results: Of 1355 patients presenting to the ED with fracture in 2015, 805 were screened, with 272 eligible for inclusion. Median age was 83 years (IQR 73–88); 69% were female, 161 participants (59%) presented with a hip or vertebral fracture and 80 (29%) participants had a documented pre‐existing osteoporosis diagnosis. Anti‐resorptive medications were indicated for 189 participants according to guidelines, though were only prescribed for one‐third of these patients ( n = 65/189, 34%). Bone mineral density testing was warranted in a further 83 patients, and undertaken in nine (11%). Only 110 participants (40%) had the words "osteoporosis" or "osteopenia" documented in their discharge summary. Discussion: Health professionals involved in the care of hospitalised patients with MTF are still missing opportunities to prevent future harms by commencing appropriate management to reduce subsequent fracture risk.